Spray Drying as a Method of Choice for Obtaining High Quality Products from Food Wastes– A Review. Issue 4 (19th May 2023) - Banožić, Marija; Vladić, Jelena; Banjari, Ines; Velić, Darko; Aladić, Krunoslav; Jokić, Stela
ABSTRACT: With globalization, growing popularization and changes in dietary habits where more processed food is consumed, a generation of food wastes and by-products has increased. Under-exploitation of by-products and waste leads to finance losses and environmental pollution although most of the waste are a rich source of bioactive compounds. Using spray drying process, extracted bioactive compounds from food wastes and by-products can be transferred into powder form, and returned to the food chain. Spray drying technique showed to be the most convenient, energy efficient and time-saving process, where a liquid is directly transformed into stable powder, which can be stored for a prolonged time or easily incorporated into other products. This review article focuses on the application of processing parameters of spray drying with specific emphasis on the production of dry extracts of food waste and their influence on powder properties. Research gaps and challenges along with possible applications are also discussed.